2001
DOI: 10.1002/ana.93.abs
|View full text |Cite
|
Sign up to set email alerts
|

A novel autosomal dominant distal myopathy with early respiratory failure: Clinico‐pathologic characteristics and exclusion of linkage to candidate genetic loci

Abstract: We describe a novel autosomal dominant myopathy presenting in mid-adult life with tibialis anterior weakness. We carried out a detailed clinical assessment of 24 individuals spanning three generations, documenting pathologic features of the muscles in 7 of the 11 affected individuals, including an autopsy study on one case. The second generation of affected individuals presented at an earlier age, and the disease progressed more rapidly than in the first generation. Lung function tests revealed progressive glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Disease onset was slightly later (mean 50.2 years) than previously described in HMERF. No other organ involvement (including heart) was found on autopsy in one patient [8].…”
Section: Historical Notesmentioning
confidence: 85%
See 2 more Smart Citations
“…Disease onset was slightly later (mean 50.2 years) than previously described in HMERF. No other organ involvement (including heart) was found on autopsy in one patient [8].…”
Section: Historical Notesmentioning
confidence: 85%
“…Desmin was present only at their periphery, in the filamentous halo, and desmin staining was increased in the cytoplasm of CB containing fibers [7]. Chinnery et al [8] reported one family with 11 affected individuals over 2 generations with congophilic CBs and rimmed-vacuolar myopathy (RVM), variable respiratory dysfunction and predominant anterolateral lower leg muscle involvement. Disease onset was slightly later (mean 50.2 years) than previously described in HMERF.…”
Section: Historical Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory failure as an early symptom in ambulant patients with inherited primary muscle diseases is uncommon. However, early respiratory failure is a frequent complication in a group of myopathies with characteristic myofibrillar lesions and cytoplasmic bodies (Jerusalem et al, 1979;Patel et al, 1983;Winter et al, 1986;Chapon et al, 1989;Edström et al, 1990;Chinnery et al, 2001;Tasca et al, 2010). These myopathies have more recently been referred to as hereditary myopathy with early respiratory failure (HMERF; OMIM#603689).…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary myopathy with early respiratory failure (HMERF, OMIM #603689) is characterized by proximal and/or distal muscle weakness, and early and severe diaphragmatic insufficiency [1][2][3][4][5]. In HMERF, respiratory failure can be a presenting symptom in an ambulant adult patient, which is not a common feature in other genetic myopathies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%